PERAN AGROINDUSTRI DALAM PEREKONOMIAN KOTA METRO - Prima Haris Retnati; Teguh Endaryanto; Sudarma Widjaya; Wan Abbas Zakaria (Indonesian Journal of Socio Economics, 2019)
This study aims to determine the role of agro-industry on the economy in Metro City, by looking at the inter-sectoral linkages in the economy. The study was conducted by survey and analysis methods used in this study were Input-Output Analysis. Data collection activities were carried out in May 2019. The results show that the agro-industry sector has links with many other sectors. Direct forward index and backward linkage index of agro-industry are less than 1. This means that the agro-industrial sector has a low linkage with other economic sectors in Metro City. Direct and indirect forward linkages index and agroindustry backward index are more than 1. This means that the agroindustry sector has a high linkage with other economic sectors in Metro City when seen directly and indirectly. So it can be said that the agro-industry sector has the ability to encourage the growth of its downstream sector and is able to attract growth in the upstream sector when seen directly and indirectly.Keywords: Agroindustry, backward linkage, forward inkage, input-output